2019
DOI: 10.3174/ajnr.a6087
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Postconcussive Reaction Time Using Transport-Based Morphometry of Diffusion Tensor Images

Abstract: BACKGROUND AND PURPOSE: Cognitive deficits are among the most commonly reported post-concussive symptoms, yet the underlying microstructural injury is poorly understood. Our aim was to discover white matter injury underlying reaction time in mild traumatic brain injury DTI by applying transport-based morphometry. MATERIALS AND METHODS: In this retrospective study, we performed DTI on 64 postconcussive patients (10-28 years of age; 69% male, 31% female) between January 2006 and March 2013. We measured the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Sensitive discrimination in the transport space is possible using Euclidean distances because 3D TBM computes a linearized version of the OT distance, described as a generalized geodesic (30). Therefore, complex, nonlinear, and spatially diffuse shifts in the image domain can be discriminated using simpler classifiers in the transport domain (28,30,36).…”
Section: Resultsmentioning
confidence: 99%
“…Sensitive discrimination in the transport space is possible using Euclidean distances because 3D TBM computes a linearized version of the OT distance, described as a generalized geodesic (30). Therefore, complex, nonlinear, and spatially diffuse shifts in the image domain can be discriminated using simpler classifiers in the transport domain (28,30,36).…”
Section: Resultsmentioning
confidence: 99%
“…A key contribution of 3D TBM is that it is generative. Unlike existing approaches, inverse transformation enables direct physical interpretation of the discovered discriminating patterns ( 19 , 22 , 28 , 29 ). This paper makes modifications and extensions to the 3D TBM framework.…”
Section: Methodsmentioning
confidence: 99%
“…We leverage these equations in conjunction with supervised machine learning to directly probe underlying biological mechanisms ( 19 ). Prior work has demonstrated that this approach can automatically discover and visualize patterns hidden to detection by existing approaches ( 19 , 22 , 28 , 29 ). This study investigates the potential of this approach in the study of neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…From this approach, a transport-based morphometry (TBM) method can also be applied to the image derived from dMRI (see also Novas et al, 2016). Kundu et al (2019) took this approach to also assess WM in mTBI showing detectable differences that otherwise would not be uncovered.…”
Section: Future Directionsmentioning
confidence: 99%